Reportase Media Asik - Syaiful Anwar; Supriadi Supriadi; Pasiska Pasiska; Sapardi Sauti; Umar Maliki; Chusnul Ngatiyah; Della Pudralisa (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2021)
This paper is included in the type of qualitative writing, where the paper wants to show that learning media reporting is easy and fun (cool). There are at least seven things that must be done in order to get the results of cool media reporting which is the theme of this paper and they are summarized as follows; get to know reportage, the media used as reportage publications, the science of writing that applies journalistic rules and patience in carrying out cool reporting activities.